Percutaneous radiofrequency ablation of hepatocellular carcinoma in a recent cohort at a tertiary cancer center: incidence and factors associated with major complications and unexpected hospitalization events - Jo, Min Geun; Lee, Min Woo; Ahn, Soohyun; Kang, Tae Wook; Song, Kyoung Doo; Cha, Dong Ik; Min, Ji Hye; Rhim, Hyunchul (Ultrasonography, 2023)
Purpose: This study aimed to assess the incidence of and factors associated with major complications, delayed discharge, and emergency room (ER) visits or readmission after percutaneous radiofrequency ablation (RFA) for single hepatocellular carcinoma (HCC) <3 cm in a recent cohort at a tertiary cancer center. Methods: A total of 188 patients with treatment-naïve single HCCs <3 cm who underwent RFA between January 2018 and April 2021 were included in the analysis. Univariable and multivariable logistic regression analyses were performed to identify the factors associated with major complications, delayed discharge, and ER visits or readmission. Local tumor progression (LTP) and overall survival were estimated using the Kaplan-Meier method and Cox proportional-hazards regression analysis. Results: Major complications occurred in 3.2% (6/188) of the patients. The longest diameter of the ablation zone was significantly larger in patients with major complications (P=0.023). Delayed discharge occurred in 5.8% (9/188) of the patients, for which albumin-bilirubin grade 3 was identified as an important determinant. No variables other than major complications were significantly associated with ER visits or readmission, which occurred in 7.0% (13/188) of the patients. Major complications, delayed discharge, and ER visits or readmission were not substantially related to the post-treatment outcomes of LTP and overall survival. Conclusion: This study confirmed RFA as a highly safe procedure for single HCCs <3 cm, despite the rapidly changing RFA techniques in the most recent cohort. A large ablation zone and poor liver function were predictors of major complications and delayed discharge, respectively.
Keywords: Complications; Hepatocellular carcinoma; Radiofrequency ablation